Protuberances. Materiality and Testimonial Function in Lesson of Darkness by Werner Herzog. - Mengoni, Angela (E|C, 2023)
In the film Lessons of Darkness (Lektionen in Finsternis 1992) Werner Herzog explores the landscape of Kuwait devastated by the burning oil wells left behind by the retiring Iraqi army at the end of the first Gulf War. The director, nevertheless, combines this extraordinary documentary images with an apocalyptic text that makes no explicit reference to the specific context and political reasons of the conflict. This was the reason why several critics and audiences accused the director of accomplishing a so-called “aesthetization of war”. The paper discusses these accusations in order to show how the film actually bears witness to specific aspects of the conflict through its own semiotic strategies and, in particular, how the emergence of materiality, both in the body of civilians and in the landscape, is the way through which the traumatic impact of war on the victims regains a visibility that was programmatically absent from the media narratives.